Factors affecting the dormancy and germination of bleeding heart [Lamprocapnos spectabilis (L.) Fukuhara] seeds. (26th February 2020) - Cho, J. S.; Jang, B. K.; Lee, S. M.; Lee, I. J.; Lee, C. H.
Abstract: Information on the optimal conditions to promote the germination of Lamprocapnos spectabilis (L.) Fukuhara seeds is limited; consequently, this study was conducted to establish the requirements to break seed dormancy and promote germination. The selected seeds had morphophysiological dormancy and had not begun embryo development. To study the dormancy breaking and embryo development processes, seeds were subjected to constant or changing temperature treatments during moist stratification. High temperature and humidity resulted in vigorous embryo growth, with the longest embryos occurring after 1 month of incubation at 20 °C. At 4 °C, the seeds required incubation period of at least 3 months to germinate. Embryo growth and germination were higher with changing high and low temperatures than under a constant temperature, and changing temperatures also considerably changed the endogenous hormone levels, embryo development and germination. Bioactive gibberellin (GA) content was higher in seeds incubated at 20 °C for 1 month, then at 4 °C for 2 months. The content of endogenous abscisic acid in seeds subjected to the same treatment decreased by 97.6% compared with that of the untreated seeds. Embryo growth and seed germination require changing high and low temperatures; however, exogenous GA3 could substitute for high temperatures, as it also causes accelerated germination. In this study, the seeds of L. spectabilis were identified as an intermediate simple type, a sub‐level of morphophysiologically dormant seeds. Abstract : Changing high and low temperatures, required for Lamprocapnos spectabilis embryo growth and seed germination, differentily change the endogenous levels of the phytohormones GAs and ABA.